Lysosomes - Associated Diseases and Methods to Study Their Function 2017
DOI: 10.5772/intechopen.70142
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Dysfunctions in Hereditary Spastic Paraplegias

Abstract: Hereditary spastic paraplegias (HSPs) comprise a heterogeneous group of inherited neurodegenerative diseases with the cardinal feature of a length-dependent degeneration of corticospinal motor axons. They are classified by their mapped genetic loci, SPG1-SPG78. Recently, lysosomal dysfunction is one of the pathomechanism for some autosomalrecessive HSPs. SPG11 is caused by loss-of-function mutations in the SPG11 gene. Its gene product is called spatacsin, which is needed for the recycling of lysosomes from aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…ZFYVE26 encodes a zinc-finger protein spastizin that is highly expressed in the brain and is a component of the adaptor-related protein complex 5 (AP5) that plays a crucial role in autophagic lysosomal reformation. Its dysfunctioning can result in the loss of neuronal cells [23,24]. Our study reports the second identified case of ZFYVE26 related spinocerebellar degeneration in the Pakistani population [25].…”
Section: Discussionmentioning
confidence: 66%
“…ZFYVE26 encodes a zinc-finger protein spastizin that is highly expressed in the brain and is a component of the adaptor-related protein complex 5 (AP5) that plays a crucial role in autophagic lysosomal reformation. Its dysfunctioning can result in the loss of neuronal cells [23,24]. Our study reports the second identified case of ZFYVE26 related spinocerebellar degeneration in the Pakistani population [25].…”
Section: Discussionmentioning
confidence: 66%